Citrulline decreases hepatic endotoxin-induced injury in fructose-induced non-alcoholic liver disease: an ex vivo study in the isolated perfused rat liver. Issue 11 (22nd June 2017) - Ouelaa, Wassila; Jegatheesan, Prasanthi; M'bouyou-Boungou, Japhète; Vicente, Christelle; Nakib, Samir; Nubret, Esther; De Bandt, Jean-Pascal
Abstract: Steatosis can sensitise the liver to various challenges and favour the development of non-alcoholic fatty liver disease (NAFLD). In this context, fructose feeding promotes endotoxin translocation from the gut, contributing to disease progression via an inflammatory process. Citrulline is protective against fructose-induced NAFLD; we hypothesised that this property might be related to its anti-inflammatory and antioxidative action against endotoxin-induced hepatic injuries. This hypothesis was evaluated in a model of perfused liver isolated from NAFLD rats. Male Sprague–Dawley rats ( n 30) were fed either a standard rodent chow or a 60 % fructose diet alone, or supplemented with citrulline (1 g/kg per d) for 4 weeks. After an evaluation of their metabolic status, fasted rats received an intraperitoneal injection of lipopolysaccharide (LPS) (2·5 mg/kg). After 1 h, the livers were isolated and perfused for 1 h to study liver function and metabolism, inflammation and oxidative status. In vivo, citrulline significantly decreased dyslipidaemia induced by a high-fructose diet and insulin resistance. In the isolated perfused rat livers, endotoxaemia resulted in higher cytolysis (alanine aminotransferase release) and higher inflammation (Toll-like receptor 4) in livers of fructose-fed rats, and it was prevented by citrulline supplementation. Oxidative stress and antioxidative defences were similar in all three groups. Amino acid exchanges and metabolism (ammonia and urea release) were only slightly different between the three groups. In this context of mild steatosis, our results suggest that fructose-induced NAFLD leads to an increased hepatic sensitivity to LPS-induced inflammation. Citrulline-induced restriction of the inflammatory process may thus contribute to the prevention of NAFLD.